A dimensão ontológica na Geografia: um paralelo entre o horizonte da crítica-radical e o pensamento de Martin Heidegger - Zadorosny, Luana Rodarte Oliveira (2019)
This study is structured around the articulation of three basic elements. The first element refers to the thematic scope and corresponds to the ontology of space as the -formal object? of research in Geographic Science. We propose it's problematization through two different methodologies that correspond with the two elements referred to in the methodological scope: the horizon of the radical/critical approach associated with marxist historical and dialectical materialism and the Heidegger's philosophy approach, which is through the hermeneutic phenomenology. These three elements in the problematization have been recorded in the historiography of Geography since the innovative movement initiated in the 1970's. In that moment both the assimilation of the ontological reflection of space with the constitution of the horizon of radical/critical approach and the assimilation of phenomenology with the Heideggerian thought in the core of the constitution of the humanistic horizon of the subject became permanent. The research addresses the topic of the ontological foundation of space and its articulation of the issue concerning nature-society relationships, through the parallel with the methods of investigation highlighted previously that, through their particular features, contribute to the theoretical arguments and debates in the field under different perspectives, scope and purpose. On the one hand, it presents a trait of ontological thinking marked by the influence of the marxist/luckácsian theories and determined essentially by the ontology of the social being. This is an ontological problematization that is carried out considering the centrality of the notion of work (or social production) as an ontological principle that is widely echoed in the analysis of the reality and in the formulation of a spatial theory in the discipline. On the other hand, it presents the basic indispensable elements to develop an ontological investigation on a phenomenological basis. The basic terms of the heideggerian project are exposed through the following elements: the ontological difference between being and beings, the analytic of being-there as a source towards investigations on the notion of being, the analysis of the structure being-in-the-world and the mundanity of the world – and, in the core of the existential analytic, the phenomenological questioning of space as a phenomenon rooted in the being-there. Both propositions are fundamentally divergent to the trait that the question about the nature-society relationships acquires as a result of their most fundamental conjectures.